Influence for Ambient Relative Humidity and Pollution on Infrared Detection of Zero Resistance Insulators - Chen, Ling; Lin, Feng; Chen, Minjiang; Huang, Xiongtao; He, Ruomei; Zheng, Yaqing (Frontiers in Energy Research, 2022)
Porcelain insulatorss plays a vital role for safety and stability operations of electric system. In a strong electric field, these insulatorss are easy to be broken down and become zero resistance insulators, which impacts the safety and stability operations of electric system. As a result, a three-dimensional zero resistance insulator model is set up based on COMSOL. To proceed, firstly, study the voltage and current density law of insulators string when ambient relative humidity, pollution degree and pollution salt composition are different. Then insulators infrared detection test is carried out in artificial fog chamber. Results show that the zero resistance insulator has the greatest influence on voltage when it is at high voltage terminal, and it has the least influence on voltage when it is in the middle position; As the relative range between non-adjacent insulators and zero resistance insulator raises, the implications for zero resistance insulator on adjacent position insulators will decrease continuously Farther is the range between different positions on the insulators and center axis of rotation, lower is the current density and temperature rise; The overall temperature rise of insulators string gradually raises due to the raise of relative humidity and pollution degree of environment. Finally, the temperature difference between zero resistance insulator and other insulators gradually raises; the research results can provide support for infrared detection of zero resistance insulators